Evaluation with trend analysis of the open surface evaporation in observed for many years: The Case Study in Nevsehir Province of Turkey - BAGDATLI, M.Cuneyt; Balli, Yigitcan (Recent Research in Science and Technology, 2020)
In this study, the trends of the climate station belonging to the Turkish General Directorate of Meteorology in the center of Nevsehir province of Turkey between 2001-2019 years were subjected to the Rho’s correlation tests of Mann Kendall and Sperman for years of maximum open surface evaporation and total open surface evaporation. According to the results of the trend analysis, the maximum open surface evaporation was 59,7 mm and the total open surface evaporation was calculated as 1013,2 mm in the center of Nevsehir Province over long period. It was observed that the average maximum temperature value was 24 oC for long years and the total precipitation average was 363,6 mm. It was observed that there was a significant increase in open surface evaporation values varying in years in spring, winter and autumn. According to the trend analysis results made for many years, a trend was not observed in the Maximum and total open surface evaporation parameters in Nevsehir province of Turkey